Cemeteries of the Great War by Sir Edwin Lutyens - Geurst, Jeroen (Rotterdam : 010 Pub., 2010)
Summary: The British architect Sir Edwin Lutyens (1869-1944) designed 140 cemeteries in the countryside of Flanders and Northern France for soldiers killed in the First World War. The cemeteries can be regarded as an imprint, as it were, of the former battlefront on the map of Europe. All are designed to principles established beforehand, including uniform gravestones, a large Stone of Remembrance and a large cross. Yet the difference in size, alignment and provenance make them all unique variations on the themes in question. The most memorable aspects are their meticulously chosen position in the landscape, the varied selection of trees and other greenery and the architecture of the entrance and shelter buildings. This illustrated book charts the history of the designs and exposes the underlying principle of order and variation in the architecture in an exhaustive landscape-architectural analysis. All 140 cemeteries are fully documented with references to the places where they are to be found.
Includes bibliographical references and index.
boek
Keywords: Lutyens, Edwin Landseer